Socio-economic situation in the region through the prism of ethnic identity: materials of sociological research in the Republic of Dagestan in 2020 - Zaripov, Airat Ya.; Huseynov, Abdurakhman H.; Maluchiev, Gadzhi S. (The New Research of Tuva, 2022)
The article examines the outcomes of a sociologic survey of the population of the Republic of Dagestan held in 2020 in order to investigate how people assessed the socio-economic situation in the region during the pandemic. A special focus was made on the opinions expressed by the members of the region’s leading ethnic groups. We have summed up the opinions on the economic situation both individuals and families saw themselves in, as well as what respondents thought on how to reach economic success, get a job, provide decent healthcare — and also how life felt from specifically ethnic viewpoints. Members of a number of ethnicities reflected on the current social and economic problems, on the opportunities and conditions of using native languages in communication, education, healthcare, as well as on ethnic self-consciousness and ethnic identification in times of crisis.Not all ethnicities shared identical feelings in this situations. Avars, Dargins and Kumyks, who had been relatively dominating in social, economic and political spheres before the pandemic, saw little change. On the contrary, smaller ethnic communities, such as Russians or Azerbaijanis, saw their economic conditions worsen, especially in employment, getting a new job in their professional field or in accordance with their specialization. This led to decreased welfare and worsened social status.The people of the region saw the overall socioeconomic situation as a little worse than satisfactory. While 1/10 of the population are convinced that they live better than their counterparts in other regions of Russia, and 1/5, on the contrary, believe that their welfare is worse than the federal average, the overwhelming majority of 70% see no difference between living standards in Dagestan and Russia’s other constituent regions.
Keywords: Dagestan; ethnicities in Dagestan; ethnic self-consciousness; ethnic identity; social well-being; living standard; pandemic